INFECTIOUS DISEASES AND THEIR PREVENTION ACROSS THE SEVEN AGES OF MAN - E. David G. McIntosh AM; L. S. Namazova-Baranova (Педиатрическая фармакология, 2012)
This paper will describe some important infectious diseases and their prevention, to illustrate the interconnectedness of people at different ages. The diseases of interest are congenital infections, bacterial meningitis, rotavirus and human papillomavirus, healthcare associated infections, and influenza. Vaccination of individuals in one age group, for example children, may confer benefits on adults and vice versa. Of particular interest is vaccination of the pregnant woman, especially with regards to pertussis and influenza.